Utilizing Deep Learning Approaches for Enhancing English Vocabulary Acquisition - fahriany fahriany (Arabic Language Education Study Program, Tarbiyah and Teacher Training, UIN Prof K.H Saifuddin Zuhri Purwokerto, 2026)
Utilizing deep learning approaches for enhancing English vocabulary acquisition has emerged as a promising innovation in the field of language learning and educational technology. Deep learning, a subset of artificial intelligence, enables machines to process and analyze large volumes of linguistic data in a way that mimics human cognitive functions. When applied to vocabulary learning, deep learning algorithms can personalize content, identify learner patterns, and adapt instructional materials based on individual progress and proficiency levels. This allows for more efficient and targeted learning experiences, especially when integrated into mobile or web-based platforms. Learners are exposed to contextual vocabulary usage, real-time feedback, and engaging multimedia resources, which together foster deeper retention and understanding. Furthermore, natural language processing (NLP), a key component of deep learning, enables systems to evaluate learner input, provide synonyms, definitions, and usage examples, and even generate exercises tailored to learners’ specific needs. Studies have shown that incorporating deep learning in vocabulary acquisition can improve motivation, increase learning speed, and support long-term memorization by reinforcing word use in meaningful contexts. This technological approach also enables educators to track student progress in real-time and adjust learning paths accordingly. As a result, deep learning is not only transforming traditional language instruction but also making English vocabulary acquisition more dynamic, interactive, and learner-centered. With continuous advancements in AI, the integration of deep learning in language education is expected to become more prevalent and impactful, offering a powerful tool for learners striving to achieve greater fluency and vocabulary mastery.